Hydraulic fracture propagation in soft coal composite reservoirs: Mechanical responses and energy dissipation mechanisms - Zhou, Aitao; He, Yizheng; Wang, Kai; Li, Bo; Wang, Yida; Yang, Yuexin (International journal of mining science and technology, 2025)
The hydraulic fractures induced in soft coal composite reservoirs have complex extension and energy evolution characteristics. In this study, the mechanism whereby gas outbursts can be eliminated by hydraulic fracturing was revealed. The combined fracturing process of a coal seam and its roof under different in situ stress and fracture spacing conditions was analysed through true triaxial physical tests and numerical simulations. The results showed that the pre-fracturing of the roof had a pressure relief effect on the coal seam, and the secondary pressure relief of the coal seam could be completed at a lower fracture initiation pressure. To ensure the continued presence of the stress shadow effect in actual projects, the fracture spacing should be maintained within the critical range influencing the fracture extension. If the vertical stress is high, a call on increasing the fracture spacing can be taken; otherwise, it must be reduced. In the early phase of fracturing, energy is mostly concentrated at the tip and surface of the fracture; however, the proportion of surface energy for subsequent fracturing is gradually reduced, and the energy is mostly used to open the formation and work on the surrounding matrix. Hydraulic fracturing creates new fractures to interconnect originally heterogeneously distributed gas zones, enabling the entire coal seam to first establish interconnected pressure equilibration, then undergo gradient-controlled depressurization. Hydraulic fracturing can homogenize the stress field and gas pressure field in the original coal seam via communication pressure equalization and reduction decompression, reduce the elastic and extension energies, increase the minimum failure energy required for instability; and realize the elimination of gas outbursts. Our findings provide some theoretical support for the efficient development of coalbed methane and the prevention and control of dynamic gas disasters in coal mines.